Depression and alcohol use disorders as precursors to death by suicide. Issue 3 (16th March 2022) - Perez, Jalessa; Beale, Eleanor; Overholser, James; Athey, Alison; Stockmeier, Craig
Abstract: The combined presence of depression with alcohol abuse can increase suicide risk. We used psychological autopsy to evaluate 101 individuals who died by suicide, to understand relationships between stressful life events, alcohol abuse, and depression. As compared to suicidal adults with depression only, individuals meeting criteria for both a depressive disorder and alcohol use disorder tended to be younger and experienced higher rates of stressful life events during the six months prior to death. Alcohol abuse likely influences interpersonal conflict, financial distress, and legal problems. Interventions focusing on managing life problems may help to reduce suicide risk.